Continental dispersal of the cassava green mite, an exotic pest in Africa, and implications for biological control - Yaninek, J.S. (1988)
The continental dispersal of an exotic spider mite species is described for the first time. The cassava green mite,Mononychellus tanajoa (Bondar) (Acari: Tetranychidae), has been found to be dispersed across the cassava belt of Africa in less than 10 years after first being discovered in 1971. This mite disperses within plants by walking, and within and between fields by drifting aerially. Widespread transportation of mite-infested plant material, however, is proposed to explain the rapid spread ofM. tanajoa in Africa. Observations of mite-infested plant material being transported in the field, and laboratory evidence of mite populations surviving up to 60 days on cassava stems removed from the field and isolated from external contaminates, support this hypothesis. The spread ofM. tanajoa in Africa as a model for future introductions on cassava suggests a pattern of movement at species-specific rates. Exotic natural enemies ofM. tanajoa, especially phytoseiid predators, are expected to spread at a rate slower than their host; consequently, large-scale and long-range releases will be needed to accelerate their spread.